Elderly Use Proprioception Rather than Visual and Vestibular Cues for Postural Motor Control - Wiesmeier, Isabella Katharina; Dalin, Daniela; Maurer, Christoph (Frontiers in Aging Neuroscience, 2015)
Multiple factors have been proposed to contribute to the deficits of postural control in the elderly. They were summarized as sensory, motor, and higher level adaptation deficits. As for the sensory deficits, known degradations include proprioceptive, visual, and vestibular channels. Using a model-based approach, we aimed to identify which of the sensory, motor and adaptation deficits mainly determine age-related changes in postural control. We analyzed postural control of 20 healthy elderly people with a mean age of 74 years. The findings were compared to data from 19 healthy young volunteers (mean age 28 years) and 16 healthy middle-aged volunteers (mean age 48 years). Postural control was characterized by spontaneous sway measures and measures of perturbed stance. Perturbations were induced by pseudorandom anterior-posterior tilts of the body support surface. As observed in other studies, we found that spontaneous sway amplitude and velocity were significantly larger, and sway frequencies were higher in elderly compared to young people. Gain profiles as a function of stimulus frequencies, amplitudes, and visual conditions, a new measure based on the transfer functions between external stimuli and body responses, were clearly different in elderly compared to young people. Based on simple feedback model simulations, we found that elderly favor proprioceptive over space cues, other than younger subjects. This may indicate that the visual and vestibular inputs for posture degrade faster with age than the proprioceptive input does. Moreover, we identified an increase in overall time delay challenging the feedback systems stability, and a decline in the amplitude of the motor feedback, probably representing the aging of the motor system. In general, these parameter differences between young and old may result from both degradation processes and compensation strategies. Our model-based findings correlated well with clinical balance scores.